2002
DOI: 10.1029/2002ja009452
|View full text |Cite
|
Sign up to set email alerts
|

Equatorial plasma bubbles observed by DMSP satellites during a full solar cycle: Toward a global climatology

Abstract: [1] We have examined more than 75,000 latitudinal profiles of plasma densities measured by ion detectors on five Defense Meteorological Satellite Program (DMSP) satellites in the evening local time (LT) sector between 1989 and 2001. This survey established detection frequencies of equatorial bubbles (EPBs) at 840 km over the recent solar cycle. The annual rate of EPB detections decreased by more than an order of magnitude from >1000 during solar maximum to <100 during solar minimum years. EPB data were divided… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

22
187
4

Year Published

2012
2012
2015
2015

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 137 publications
(226 citation statements)
references
References 38 publications
22
187
4
Order By: Relevance
“…(4) indicates that these effects on the growth rate should be anticorrelated with the longitudinal dependence of the field strength of the magnetic field observed in the lower panel of Fig. 2, for a constant value of the eastward electric field (Huang et al, 2001;Burke et al, 2004a, b). Equation (4) also indicates that the growth rate increases when P E decreases.…”
Section: Discussionmentioning
confidence: 78%
See 3 more Smart Citations
“…(4) indicates that these effects on the growth rate should be anticorrelated with the longitudinal dependence of the field strength of the magnetic field observed in the lower panel of Fig. 2, for a constant value of the eastward electric field (Huang et al, 2001;Burke et al, 2004a, b). Equation (4) also indicates that the growth rate increases when P E decreases.…”
Section: Discussionmentioning
confidence: 78%
“…It has been remarked in Sect. 1 that Huang et al (2002) and Burke et al (2004a, b) based their analyses on a different parameter. In principle, differences between corresponding results could be due to the respective measurement periods and the associated solar activities, orbital characteristics of the satellites, instrumentation, processing techniques developed by different authors, etc.…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations
“…There have been many studies on the occurrence characteristics of ionospheric density irregularities using groundbased measurements (Rastogi, 1980;Abdu, 2001), satellitebased in situ measurements (Watanabe and Oya, 1986;Huang et al, 2002;Burke et al, 2004), and topside sounders (Maruyama and Matuura, 1984), and many important features of these have been reported including temporal variations (Sahai et al, 2000;Huang et al, 2002), seasonallongitudinal variability (Burke et al, 2004), several-day variation, and day-to-day variation (Basu et al, 1996) though several enigmatic features of them are yet to be revealed (Thampi et al, 2009). However, studies on continuous and global characteristic features of ionospheric plasma irregularities are very scanty due to the fact that the global coverage is difficult to obtain from ground-based observations.…”
Section: Introductionmentioning
confidence: 99%